Cystic fibrosis transmembrane conductance regulator mutations that disrupt nucleotide binding. - Logan, J (1994)
Increasing evidence suggests heterogeneity in the molecular pathogenesis of cystic fibrosis (CF). Mutations such as deletion of phenylalanine at position 508 (delta F508) within the cystic fibrosis transmembrane conductance regulator (CFTR), for example, appear to cause disease by abrogating normal biosynthetic processing, a mechanism which results in retention and degradation of the mutant protein within the endoplasmic reticulum. Other mutations, such as the relatively common glycine-->aspartic acid replacement at CFTR position 551 (G551D) appear to be normally processed, and therefore must cause disease through some other mechanism. Because delta F508 and G551D both occur within a predicted nucleotide binding domain (NBD) of the CFTR, we tested the influence of these mutations on nucleotide binding by the protein. We found that G551D and the corresponding mutation in the CFTR second nucleotide binding domain, G1349D, led to decreased nucleotide binding by CFTR NBDs, while the delta F508 mutation did not alter nucleotide binding. These results implicate defective ATP binding as contributing to the pathogenic mechanism of a relatively common mutation leading to CF, and suggest that structural integrity of a highly conserved region present in over 30 prokaryotic and eukaryotic nucleotide binding domains may be critical for normal nucleotide binding.